Inter-industry wage differentials and the gender wage gap: evidence from European countries - Gannon, Brenda; Plasman, Robert; Rycx, Francois; Tojerow, Ilan (Economic & Social Studies, 2007)
This study analyses the interaction between inter-industry wage differentials and the gender wage gap in six European countries using a unique harmonised matched employer-employee data set, the 1995 European Structure of Earnings Survey. Findings show the existence of significant inter-industry wage differentials in all countries for both sexes. While their structure is quite similar for men and women and across countries, their dispersion is significantly larger in countries with decentralised bargaining. Further results indicate that industry effects on the gender wage gap fluctuate sharply across European countries. In particular, our results show that combined industry effects explain 29 per cent of the gender wage gap in Ireland.
Keywords: Wage differentials; Gender; Europe; Ireland; Inter-industry